2010
DOI: 10.1021/jf102576j
|View full text |Cite
|
Sign up to set email alerts
|

On the Inhibitor Effects of Bergamot Juice Flavonoids Binding to the 3-Hydroxy-3-methylglutaryl-CoA Reductase (HMGR) Enzyme

Abstract: Density functional theory was applied to study the binding mode of new flavonoids as possible inhibitors of the 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR), an enzyme that catalyzes the four-electron reduction of HMGCoA to mevalonate, the committed step in the biosynthesis of sterols. The investigated flavonoid conjugates brutieridin and melitidin were recently quantified in the bergamot fruit extracts and identified to be structural analogues of statins, lipids concentration lowering drugs that inhibit HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 40 publications
1
39
0
1
Order By: Relevance
“…It might be argued that chlorogenic acid and naringenin substitute the HMG moiety of HMGCoA in a similar way to that reported by other authors [31]. For example, a similar effect has been also described for the flavonoid conjugates from bergamot juice (brutieridin and melitidin), which seemed to invade the HMG-binding site, both compounds being good candidates for the inhibition of HMGCR [32].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…It might be argued that chlorogenic acid and naringenin substitute the HMG moiety of HMGCoA in a similar way to that reported by other authors [31]. For example, a similar effect has been also described for the flavonoid conjugates from bergamot juice (brutieridin and melitidin), which seemed to invade the HMG-binding site, both compounds being good candidates for the inhibition of HMGCR [32].…”
Section: Resultssupporting
confidence: 76%
“…These in vivo studies reported an inhibition of the activity of HMGCR after the intake of phenolic compounds, but did not explain possible action mechanisms. The molecular modelling described in the present paper explains the formation of the complexes between the chlorogenic acid and naringenin, which would compete with the HMG moiety of the HMGCoA and show a similar effect to that of the flavonoids of bergamot juice [32]. Although these compounds would exert a hypocholesterolemic effect in vivo by inhibiting the activity of HMGCR, in our study the intake of chlorogenic acid and naringenin from tomato juice was very low (1.3 and 0.5 mg/kg of body weight, respectively).…”
Section: Discussionmentioning
confidence: 74%
“…They suggested the involvement of the HMG group in the inhibitory effect on HMG-CoA reductase because these flavonoids had similar structures to that of simvastatin, a known inhibitor for HMG-CoA reductase [24]. However, our current study showed that the compounds 7 and 9-11 without the HMG group had more potent activity to inhibit HMG-CoA reductase in vitro than the compound 8 with the HMG moiety.…”
Section: Discussionmentioning
confidence: 64%
“…Many studies describe the biosynthesis pathway of triterpenoid saponins in three parts [14,15]. Part I is upstream isopentenyl diphosphate (IPP) and dimethylallyl pyrophosphate (DMAPP) biosynthesis [16,17], part II is the midstream carbocyclic of triterpenoid biosynthesis [18], and part III is the downstream modification pathway of complex functional groups in triterpenoid carbocyclic [19]. Genes upstream and midstream of the pathway have been intensively studied [20,21], but the specific downstream genes involved in catalysing triterpenoid saponin biosynthesis have yet to be revealed.…”
Section: Introductionmentioning
confidence: 99%